ANALISIS HERMENEUTIKA NILAI KEKELUARGAAN DAN PENDIDIKAN DALAM NOVEL RASA KARYA TERE LIYE - Manshur, Ali; Nafisatul Munawaroh, Umu (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The phenomenon of the appearance of various interpretations used by readers of Tere Liye's novel Rasa makes the meaning intended by the author for readers increasingly different from one reader to another. The focus behind the emergence of problems in interpreting the meaning contained in Tere Liye's novel Rasa in everyday life is 1) how is the hermeneutic analysis of family values ??in Tere Liye's novel Rasa? 2) how is the hermeneutic analysis of the educational value of Tere Liye's novel Rasa? The aims of this study are: 1) to describe the hermeneutics of family values ??2) to describe the hermeneutics of educational values ??in Tere Liye's novel Rasa. This study uses a qualitative descriptive method that can help identify various factors and information in interpreting a meaning contained in Tere Liye's novel Rasa. The technique used to obtain data is the note-taking technique. The analysis used is the Miles and Huberman model: data collection, data reduction, data presentation, and conclusion/verification. The validity of the data used is a triangulation technique. Based on the results of the research data analysis and discussion, it can be concluded that there are 15 data on family values ??and 70 data on educational values.